Knowledge of Housewives Regarding Non Steroid Anti Inflammatory Drug Use on Joint Pain in Hegarmanah Village Jatinangor - Gondopurwanto, Adi Mulyono; Kuswinarti, Kuswinarti; Wibisono, Yusuf (Althea Medical Journal, 2016)
Background: Joint pain is frequently found in daily life activities. The prevalence of joint pain increases within the age. One of the medicine used for joint pain is non-steroidal anti-inflammatory drug (NSAID). In connection with inappropriate usage and their side effects, this study aimed to seek the extent ofhousewivesâ knowledge on the use of NSAID for joint pain in Hegarmanah village, Jatinangor subdistrict.Methods: This cross-sectional descriptive study was conducted in October 2013 to the housewives resided in Hegarmanah village, Jatinangor subdistrict, West Java. Questionaire sheet was distributed to each of 110 housewives that had been stratifiedly with randomized sample. The questionaire contained identity, age, education level, and knowledge of NSAID in related to joint pain.Results: Based on the data collected, 73 subjects had adequate level of the knowledge and 37 subjects were in a poor level of the knowledge. The proportion of respondents who knew that joint pain was the pain occurs in the joint was 99.1%, the proportion of respondents who knew that the pain relieving drugs are called NSAID group was 40.9%, the proportion of respondents who knew that NSAID had a side-effect was 73.6%, and the proportion of respondents who knew that the side-effect of NSAID is abdominal pain was 61.8%.Conclusions: Most of the housewives in Hegarmanah Subdistrict have adequate knowledge in the use ofNSAID for joint pain relief. [AMJ.2016;3(1):115â9]DOI:Â 10.15850/amj.v3n1.711